Assessment of Professional Learning Teams: The College of Education Experience - D. Alimen, Prof. Ma. Cecilia (International Journal of Scientific Research and Management (IJSRM), 2023)
In the recent professional development training, professional learning communities were recognized as a strategy for school development and student achievement. This descriptive exploratory study establishes the practices of PLT in the Education Department, College of Liberal Arts, Science, and Education (CLASE). The researchers investigated leadership and teacher collaboration, professional learning, and development attempts. All 21-full time faculty members were the participants in this study. They answered the 52-item Likert-type questionnaire adopted from Antinluoma, Ilomaki, and Toom (2021). Researchers sent Informed consent forms to the participants before the conduct of the study. Results showed that the academic supervisor is described as a visionary leader who started the positive creation, shared the leadership, and created the commitment to common departmental goals. Change in leadership is seen to have a positive effect. Decision-making processes were collaborative, cooperative, inclusive, and democratic. Relationship among faculty members is based on mutual trust and openness. Each faculty is encouraged to express their opinions. Shared responsibility for faculty members' peer mentoring, encouragement, cooperation, and peer teaching was practiced in both online and face-to-face strategies. Frequent online collaboration and communication were channels of effective professional learning engagements. The findings of this study present how other educational institutions can learn from the data in creating an environment that is proactive for teachers' professional practice, given the background of the professional learning communities' construct by which teachers can gain professional learning and development. The PLT serves as a process from which the department must continuously derive its development mechanism.